Strain improvement of Phosphate solubilizing fungal strains for the production of lipase - Ilyas, Jayaraman Rajeshkumar and *M.H. Muhammad (International Multidisciplinary Research Journal, 2011)
<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">A laboratory study was conducted to isolate, investigate and enhance the phosphate solubilization efficiency of certain isolated fungal strains viz., Aspergillus niger, Aspergillus fumigatus, Penicillium sp. These fungal strains were isolated from the rhizosphere of paddy fields in Tamilnadu, India and screened for phosphate solubilization. The <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">enhancement of Lipase activity <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">of these strains was studied through mutagenesis: UV, sodium azide and ethyl methane sulphonate. The mutant ANuv50 exhibited 32.72% increased efficiency for <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">Lipase activity in the presence of sucrose as a carbon source and 91.49%<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;"> increased efficiency for <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">Lipase activity in the presence of olive oil as a carbon source<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;"> compared to the wild strains. Similarly, the <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">Lipase activity <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">by sodium azide mutant (ANsa90) was 61.11% higher <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">in the presence of sucrose as a carbon source, 107.60%<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;"> higher <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">in the presence of olive oil as a carbon source<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;"> and EMS mutant (ANems150) was 137.65% higher <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">in the presence of sucrose as a carbon source, 98.93%<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;"> higher <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">in the presence of olive oil as a carbon source<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;"> than the wild strain. The efficient strains were further studied for the effect of carbon and nitrogen source on <span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: Calibri; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes; mso-bidi-font-weight: bold;">Lipase activity<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">. Significance of the findings is discussed in detail.